Malaysian herbs in contraception : public perception - Wan Nazatul Shima Shahidan; Tuan Nadrah Naim Tuan Ismail; Kannan Thirumulu Ponnuraj (Penerbit Universiti Kebangsaan Malaysia, 2022)
Medicinal plants have been used in Malaysia for a long time ago. These plants have been marketed as herbal product and used in the traditional healthcare system because of its positive therapeutic effects. This paper discusses particularly several types of Malaysian herbs that are traditionally used for contraception and scientific studies related to its pharmaceutical properties showing its use among the public for its anti-fertility effects. Even though several methods of contraception have been promoted for family planning, yet, the perception of the public on the usage of synthetic steroidal contraceptives due to its serious adverse effects has made them focus on indigenous plants. Contraceptives drug-containing oestrogen and progesterone have proven to be effective and popular, However, the side effects of these drugs have sparked the idea of scientists to develop newer molecules from medicinal plants. Therefore, it is necessary to investigate in-depth qualitative research on conceptions and concerns about traditional contraceptive methods using herbal ingredients among Malaysians.